Epidemiological Profile of Exogenous Drug Intoxication in Brasília - Soares, Jéssica Yohanna Silva; Lima, Beatriz Matos de; Verri, Igor Araújo; Oliveira, Stefan Vilges de (Journal of Health Care, 2021)
Introduction: In Brazil, exogenous intoxications are extremely relevant public health problems, since they have a high frequency and morbidity in the general population of the country. Aim: To describe effective intervention measures to reduce cases and deaths from drug exogenous intoxication based on the epidemiological profile of these intoxications in the city of Brasilia-DF. Method: an epidemiological, descriptive study, where data from the Information System for Notifiable Diseases were analyzed, referring to the city of Brasilia-DF, including the reported cases of exogenous drug intoxication in the period from 2011 to 2017, were analyzed. To support the discussion and the intervention proposal, a literature review was carried out on Scielo and LILACS databases. Results: 22 publications were selected after applying the analysis criteria and served as the basis for the intervention proposal of this article. Conclusion: We note the importance of strategies such as the promotion of quality of life, education, protection, recovery for the prevention of suicide, implementation of child protection medication packaging, among other intervention strategie